The impact of the Health Technology Board for Scotland's grading model on referrals to ophthalmology services. Issue 7 (17th June 2005) - Philip, S; Cowie, L M; Olson, J A
Abstract : Aim: To ascertain the impact of the Health Technology Board for Scotland's grading model on referrals to ophthalmology services. Methods: An analysis was performed of the screening outcomes of 5575 consecutive patients, who were screened by the Grampian Diabetic Retinopathy Screening Programme between March and September 2003 according to the recommendations of the Health Technology Board and the Scottish Diabetic Retinopathy Grading Scheme 2003. Results: 3066 (55%) were male. The median age was 65 years. 5.4% were passed on to the level 3 grader and 3.4% were finally referred to ophthalmology services. 2.3% required re-screening in 6 months; 85% were screened without mydriasis; 11.9% had ungradeable images despite a staged mydriasis protocol. Time to complete grading was 32 days (22–45). Conclusion: The impact of the Health Technology Board for Scotland's recommendations on referrals to ophthalmology services is modest and should be containable within existing resources.